ATTENTION TO YOUTH AND CHILDREN IS AN INVESTMENT IN THE FUTURE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Children always need love and care. The full guarantee of their rights and freedoms is extremely important for the formation of a person, the state and society's perspective.